2019
DOI: 10.30534/ijatcse/2019/66852019
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Views on E-learning and Knowledge of Learning Platforms: Case of a Professional License at the Higher Normal School of Casablanca

Abstract: The purpose of this study is to analyze students' opinions about online education. A questionnaire of 13 mixed questions was ad-ministered for this purpose to 88 students belonging to the three levels of a professional teaching license. The variables are: the importance and the advantages of putting courses online, the impact on the quality of training, the knowledge and use of learning platforms by students and the difficulties of integrating online courses into training. The results show that 80% of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Satisfaction is defined as perception of individuals about what represent extent their needs, goals and desires are met [52]. According to [53] found that traditional education technologies affect student satisfaction through student involvement and education performance that social media practices reinforce these effects. The use of social media creates an easy relationship between "group members that explains their satisfaction from active collaborative learning and improves their learning performance".…”
Section: Student Satisfactionmentioning
confidence: 99%
“…Satisfaction is defined as perception of individuals about what represent extent their needs, goals and desires are met [52]. According to [53] found that traditional education technologies affect student satisfaction through student involvement and education performance that social media practices reinforce these effects. The use of social media creates an easy relationship between "group members that explains their satisfaction from active collaborative learning and improves their learning performance".…”
Section: Student Satisfactionmentioning
confidence: 99%
“…This study also demonstrates that, similar to the research by Mohammadyari and Singh [42], the CPA learning system may offer a supportive learning environment and flexibility in terms of place and time, as well as support the user. Tingoy [43] and Ouhrir et al [44] found that Moodle increased student performance, with students receiving a score of at least 80% after using it in their learning.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the values it brings to pedagogy, instructors in higher education are beginning to devote their resources including effort and time utilizing the tools to enrich and mediate student learning [8]. about higher education perspective, several scholars suggest the deployment of social media which simplifies social education inside classes [9][10][11], enhances active learning by inspiring both learners and instructors to interact among each other [12], then promotes the learning activities that are students-centered [13]. Through literature, major social media use that is frequently examined is continuous connectivity and its value it provides to the higher education institutions that improves student communication and learning [14], which presents the learning type that is based on learners demands [15].…”
Section: Educational Use Of Social Mediamentioning
confidence: 99%